Model Bimbingan Keagamaan Berbasis Syukur untuk Mengatasi Fomo (Fear of Missing Out) di Era Digital - Umi Marwati (Jurnal Muria Research Guidance and Counseling (MRGC), 2026)
This study aims to analyze the gratitude-based religious model as an effort to overcome Fear of Missing Out (FOMO) in the digital era. FOMO arises due to the high use of social media. Individuals feel left behind in the experiences that others are experiencing. The novelty of this article is the integration of the concept of gratitude. Using the literature study method by examining various literature related to FOMO, gratitude, digital media, and religious guidance. The results of the study show that fostering gratitude can increase self-acceptance, suppress social comparison tendencies, and foster psychological calm. Religious guidance with gratitude is effective in strengthening self-control in the use of social media. Thus, this model is relevant to be used as a strategy to assist the community in dealing with psychological impacts in the digital era.